A reappraisal of the monophyly of the genus Pseudomonocelis Meixner, 1943 (Platyhelminthes: Proseriata), with the description of a new species from the Mediterranean - Casu, Marco; Cossu, Piero; Sanna, Daria; Lai, Tiziana; Scarpa, Fabio; Curini-Galletti, Marco (Zootaxa, 2011)
Pseudomonocelis paupercula nov. sp. is described from brackish-water habitats of the Mediterranean. It is distinguished from other members of the genus by the copulatory organ provided with a stylet, combined with lack of vagina and presence of a muscular organ close to the female pore. Its phylogenetic relationships have been investigated sequencing complete 18S rRNA gene and partial 28S rRNA gene, spanning variable domains D1-D6. Both BI and ML suggest a sistertaxon relationships of P. paupercula nov. sp. with the east African P. cf cavernicola. However, statistical support is low. Conversely, MP indicates P. paupercula nov. sp. as sister-taxon to all the remaining Pseudomonocelis and Minona ilenae. Overall, results of the combined analysis do not support the monophyly of the genus Pseudomonocelis. The need for wider molecular and taxonomic sampling is stressed.